Long fluororesin film, metal-coated laminated board, and circuit board
By using fluororesin with a small number of unstable functional groups and optimizing the manufacturing method, the problem of poor deformation and uniformity when bonding with the metal foil is solved, and a fluororesin strip film with high adhesion and uniformity is achieved.
Patent Information
- Application Number
- CN202380054017.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-22
- Filing Date
- 2023-07-24
- Publication Date
- 2025-02-28
AI Technical Summary
The existing fluororesin film is prone to deformation when bonded to metal foil, resulting in poor uniformity of the film and affecting electrical properties.
A long film was made of fluororesin with less than 350 unstable functional groups, and the uniformity of the film thickness in the width direction was ensured by adjusting the manufacturing method, and the difference between the maximum value and the average value was within 2 μm.
Good adhesion and uniformity between the fluororesin film and the metal foil are achieved, and the disadvantages during lamination are reduced, and the stability of characteristic impedance is improved.
Smart Images

Figure CN119546678A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a fluororesin long film, a metal-clad laminate, and a circuit board. Background Art
[0002] Epoxy resins and polyimide resins are widely used as insulating layers in circuit substrates. In recent years, for high-frequency circuit substrates used in applications in the high-frequency range of tens of gigahertz, some structures in which a fluororesin insulating layer is formed on a metal foil have been proposed from the perspective of dielectric properties and hygroscopicity (Patent Document 1). In order to obtain a low transmission loss substrate that is less likely to cause disconnection of the signal line, the fluororesin film used for this purpose is required to be bonded to the metal foil without deformation.
[0003] When a long film is produced by extrusion molding in which a resin is melted and molded, attempts have also been made to obtain uniformity in the thickness of the resin (Patent Documents 2 and 3).
[0004] As fluororesins, resins having a reduced number of unstable functional groups are known (Patent Document 4).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 2021-160856
[0008] Patent Document 2: Japanese Patent Application Laid-Open No. 2012-187874
[0009] Patent Document 3: Japanese Patent Application Laid-Open No. 2012-118238
[0010] Patent Document 4: Japanese Patent Application Laid-Open No. 2009-059690 Summary of the invention
[0011] Problems to be solved by the invention
[0012] An object of the present disclosure is to provide a long fluororesin film which has high film uniformity and does not deform when bonded to a metal foil.
[0013] Means for solving problems
[0014] The present disclosure relates to a fluororesin long strip film, characterized in that it is composed of 6 The film is composed of a fluororesin having less than 350 unstable functional groups per carbon atom, and the difference (ba) between the maximum value (b) of the average film thickness at 12 points in the traveling direction of 5 mm in the film width direction and the average film thickness of the entire surface relative to the average film thickness (a) of the entire surface is within 2 μm.
[0015] The fluororesin preferably includes tetrafluoroethylene-perfluoroalkylvinyl ether (PFA) or tetrafluoroethylene-hexafluoropropylene (FEP).
[0016] For the above fluororesins, 6 The number of unstable functional groups per carbon atom is preferably less than 20.
[0017] It is preferred that the bonding strength of the fluororesin long film when bonded to a metal foil having a surface roughness Rz of 1.5 μm or less is 0.8 N / mm or more.
[0018] The above-mentioned fluororesin long film is preferably used for a metal-clad laminate.
[0019] The present disclosure also relates to a metal-clad laminate having a metal foil and the fluororesin film according to claim 1 or 2 as essential layers.
[0020] The above-mentioned metal-coated laminate preferably also has a layer other than the metal foil and the fluororesin film, and the layer other than the metal foil and the fluororesin film is at least one selected from the group consisting of polyimide, liquid crystal polymer, polyphenylene sulfide, cycloolefin polymer, polystyrene, epoxy resin, bismaleimide, polyphenylene oxide, polyphenylene ether and polybutadiene.
[0021] The metal foil preferably has a surface roughness Rz of 1.5 μm or less.
[0022] The bonding strength between the metal foil and the fluororesin film is preferably 0.8 N / mm or more.
[0023] The present disclosure also relates to a circuit board, characterized in that it includes the metal-clad laminate described above.
[0024] Effects of the Invention
[0025] The fluororesin film of the present disclosure has the effect of rarely causing defects during lamination and also achieving good adhesion with a metal foil. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram for explaining the method of measuring the average film thickness of the present invention. DETAILED DESCRIPTION
[0027] Hereinafter, the present disclosure will be described in detail.
[0028] In the case of known fluororesin films, when they are actually used by pasting with metal foil, the films are deformed and it is difficult to evenly adhere them. In particular, it is known that insufficient uniformity of lamination may affect the electrical properties of laminates used in the electrical and electronic fields.
[0029] In the case of manufacturing a film by extrusion melt molding, due to uneven thickness, not only at the end and center of the film, but also in the center, the thickness will be different. In the case of a rolled film, a convex band-like protrusion called a gauge band will be produced. If there is a gauge band, a poor appearance and relaxation / wrinkles of the film during transportation during film formation will occur, resulting in a poor appearance in the form of a broken line. In particular, in the case of fluororesins, it is known that it is difficult to make the film uniform, unlike other resins. It is speculated that this is because, unlike other resins, the surface free energy is small, so when the end of the resin flowing out of the T-die contacts the initial roller, it is difficult to evenly unfold on the roller surface.
[0030] In addition, when the film is used to make a laminate, as a countermeasure for film sag / wrinkles, tension needs to be applied to the film for lamination, which causes residual strain and curling of the laminate. Furthermore, when used for printed circuit boards, it also causes uneven bonding and disconnection of signal lines.
[0031] In particular, in a laminated board composed of a fluororesin film and a metal foil, it is required to keep the characteristic impedance within a specific range. A method for controlling such characteristic impedance was studied, and it was found that the uniformity of the film thickness of the fluororesin film is important, and it was clarified that the fluororesin film disclosed in the present invention is particularly preferred.
[0032] The purpose of the present disclosure is to obtain a film that can reduce streaking and adhere evenly to a metal foil. To this end, it was found that by adjusting the film manufacturing method and using a resin with less unstable functional groups as the resin used, the generation of streaking can be suppressed, thereby completing the present disclosure.
[0033] The present disclosure relates to a fluororesin long strip film, characterized in that it is composed of 6 The fluororesin has less than 350 unstable functional groups per carbon atom, and the difference between the maximum average film thickness in the running direction measured every 5 mm in the width direction and the average film thickness of the entire surface is within 2 μm. These points are described in detail below.
[0034] (Long strip film)
[0035] The fluororesin film disclosed in the present invention is a long strip film. The long strip refers to a length of 3 m or more. The width of the film is not particularly limited, but is preferably 20 cm or more, more preferably 50 cm or more, and most preferably 120 cm or more. In addition, it is preferably a roll film.
[0036] The thickness of such a long fluororesin film is preferably in the range of 12.5 μm to 150 μm. The fluororesin film in such a thickness range can be particularly suitably used for the above-mentioned purposes.
[0037] The above-mentioned thickness refers to the average film thickness of the entire surface described in detail below.
[0038] In such a long fluororesin film, the above-mentioned problems caused by the occurrence of streaks are likely to occur. Therefore, it is particularly important to suppress the streaks.
[0039] (The difference between the maximum value of the average film thickness in the running direction measured every 5 mm in the width direction and the average film thickness of the entire surface is within 2 μm)
[0040] This condition shows the absence of ribs as a specific value. More specifically, it means that there is no extremely thick part compared to the average film thickness. When measuring such a parameter, the thickness is measured at 12 locations every 5 mm in the width direction and every 20 cm in the travel direction. Then, for the same width direction, the thickness of the 12 locations is averaged in the travel direction. These values become the average of the film thickness in the travel direction measured every 5 mm in the width direction.
[0041] Then, the arithmetic average of all the values of the film thickness average in the running direction measured every 5 mm in the width direction was taken as the film thickness average of the entire surface.
[0042] When the average film thickness of the entire surface obtained in this way is compared with the maximum value of the average film thickness in the traveling direction measured every 5 mm in the width direction, the point that the maximum value of the average film thickness in the traveling direction every 5 mm in the width direction is less than the average value + 2 μm is the key point in the present disclosure.
[0043] This means that the film has a very high uniformity of thickness. If the film has such a high uniformity, when the long film is rolled up, the difference in thickness in this state is small, so the film with high uniformity can be rolled up in a good state. Therefore, it is preferred from the aspect of not easily causing the disadvantages caused by the subsequent lamination with the metal foil. Furthermore, the characteristic impedance can be made into a good range.
[0044] Furthermore, a metal-coated laminate laminated with a metal foil is prone to curling. However, a metal-coated laminate obtained by using the long fluororesin film of the present disclosure also has a favorable effect of being less likely to curl.
[0045] The method for obtaining such a film will be described later.
[0046] (Fluororesin)
[0047] In the fluororesin constituting the fluororesin film of the present disclosure, for every 1×10 6The number of unstable functional groups in the main chain carbon atoms is less than 350. That is, the number of unstable functional groups of the fluororesin is small. Fluororesin is prone to produce unstable functional groups during polymerization, and such unstable functional groups are prone to produce gas due to heat melting during film molding. Such gas generation may become the cause of uneven thickness of the fluororesin film, so it is preferably composed of a fluororesin with few such unstable functional groups.
[0048] For such fluororesins with unstable functional groups within a specific numerical range, there are methods for making them by adjusting the conditions during manufacturing (during polymerization reaction), methods for reducing the number of unstable functional groups by subjecting the polymerized fluororesins to fluorine gas treatment, heat treatment, supercritical gas extraction treatment, etc. From the perspective of excellent treatment efficiency and the aspect that a part or all of the unstable functional groups are converted into -CF3 to become stable terminal groups, fluorine gas treatment (fluorination treatment) is preferred. If a fluororesin with a reduced number of unstable functional groups is used, it is preferred from the perspective of reducing the electrostatic tangent and reducing the loss of electrical signals.
[0049] The fluororesin disclosed herein has a 6 The number of unstable functional groups per carbon atom is less than 350.
[0050] By reducing the number of unstable functional groups in this manner, gas generation during melt molding can be suppressed, and uneven thickness caused by drift of the molten resin due to gas stagnating near the slit of the T-die can be suppressed.
[0051] The number of unstable functional groups is 1×10 6 The number of main chain carbon atoms is more preferably less than 250, further preferably less than 100, further preferably less than 20, and most preferably less than 10.
[0052] Specific examples of the unstable functional group include -COF, -COOH free (free COOH), -COOH bonded (associated -COOH), -CH2OH, -CONH2, and -COOCH3.
[0053] Specifically, the number of unstable functional groups is measured by the following method. First, a fluororesin is melted and compression molded to prepare a film having a thickness of 0.25 mm to 0.3 mm. The film is analyzed by Fourier transform infrared spectroscopy to obtain an infrared absorption spectrum of the fluororesin and a differential spectrum from a background spectrum of a fully fluorinated resin without a functional group.
[0054] The following formula (A) is used to calculate the absorption peak of a specific functional group in the fluororesin per 1×10 6 The number of unstable functional groups per carbon atom.
[0055] N=I×K / t(A)
[0056] I: Absorbance
[0057] K: Correction coefficient
[0058] t: film thickness (mm)
[0059] For reference, regarding the unstable functional groups in this specification, the absorption frequency, molar absorption coefficient and correction coefficient are shown in Table 1. In addition, the molar absorption coefficient is determined from the FT-IR measurement data of the low molecular model compound.
[0060] [Table 1]
[0061]
[0062] The fluorination treatment can be performed by bringing the fluorine-containing compound into contact with the fluorine-containing resin which has not been fluorinated.
[0063] The fluorine-containing compound is not particularly limited, and a fluorine radical source that generates fluorine radicals under fluorination conditions can be cited. As the fluorine radical source, F2 gas, CoF3, AgF2, UF6, OF2, N2F2, CF3OF, fluorinated halogens (e.g., IF5, ClF3), etc. can be cited.
[0064] The fluorine radical source such as the F2 gas may be a fluorine radical source of 100% concentration, but is preferably mixed with an inert gas and diluted to 5% to 50% by mass, more preferably diluted to 15% to 30% by mass. As the inert gas, nitrogen, helium, argon, etc. may be cited, and nitrogen is preferred from an economical aspect.
[0065] The conditions of the fluorination treatment are not particularly limited, and the fluorinated resin in a molten state may be brought into contact with the fluorine-containing compound, but it may be generally carried out at a temperature below the melting point of the fluorinated resin, preferably at 20°C to 220°C, and more preferably at 100°C to 200°C. The fluorination treatment is generally carried out for 1 hour to 30 hours, preferably for 5 hours to 25 hours. The fluorination treatment is preferably a treatment in which the fluorinated resin that has not been subjected to fluorination treatment is brought into contact with fluorine gas (F2 gas).
[0066] In the present specification, the content of each monomer unit constituting the fluororesin can be calculated by appropriately combining NMR, FT-IR, elemental analysis, and fluorescent X-ray analysis according to the types of monomers.
[0067] The resin constituting the fluororesin film of the present disclosure is not particularly limited, as long as it is a polymer containing fluorine atoms in part. Fluororesins are more preferably fluororesins that can be melt-molded, and examples thereof include tetrafluoroethylene-perfluoroalkyl vinyl ether copolymers (PFA), copolymers having chlorotrifluoroethylene (CTFE) units (CTFE copolymers), tetrafluoroethylene-hexafluoropropylene copolymers (FEP), tetrafluoroethylene-ethylene copolymers (ETFE), polychlorotrifluoroethylene (PCTFE), chlorotrifluoroethylene-ethylene copolymers (ECTFE), polyvinylidene fluoride (PVDF) and polyvinyl fluoride (PVF), tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymers (THV), tetrafluoroethylene-vinylidene fluoride copolymers, etc.
[0068] Among these melt-moldable fluororesins, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymers (PFA) and tetrafluoroethylene-hexafluoropropylene copolymers (FEP) are preferred.
[0069] By using the above-mentioned melt-moldable fluororesin, melt molding is possible, so the processing cost can be suppressed compared with the case of using PTFE. Furthermore, the adhesion when bonding with metal foil can be improved.
[0070] The melting point of PFA is preferably 180 to 340° C., more preferably 230 to 330° C., and further preferably 280 to 320° C. The melting point is a temperature corresponding to a maximum value in a heat of fusion curve when the temperature is increased at a rate of 10° C. / min using a differential scanning calorimeter [DSC].
[0071] The above-mentioned PFA is not particularly limited, and preferably a copolymer in which the molar ratio of TFE units to PAVE units (TFE units / PAVE units) is 70 / 30 or more and less than 99.5 / 0.5. A more preferred molar ratio is 70 / 30 or more and 98.9 / 1.1 or less, and a further preferred molar ratio is 80 / 20 or more and 98.5 / 1.5 or less. If the TFE unit is too few, the mechanical properties tend to decrease; if it is too much, the melting point is too high and the moldability tends to decrease. The above-mentioned PFA can be a copolymer consisting only of TFE and PAVE, and is also preferably a copolymer in which the monomer units from monomers copolymerizable with TFE and PAVE are 0.1 mol% to 10 mol%, and the total of TFE units and PAVE units is 90 mol% to 99.9 mol%. As monomers copolymerizable with TFE and PAVE, HFP, CZ3Z4=CZ5(CF2) can be mentioned. nA vinyl monomer represented by Z6 (wherein Z3, Z4 and Z5 are the same or different and represent a hydrogen atom or a fluorine atom, Z6 represents a hydrogen atom, a fluorine atom or a chlorine atom, and n represents an integer of 2 to 10), and an alkyl perfluorovinyl ether derivative represented by CF2=CF-OCH2-Rf7 (wherein Rf7 represents a perfluoroalkyl group having 1 to 5 carbon atoms). Other copolymerizable monomers include, for example, cyclic hydrocarbon monomers having an anhydride group, and anhydride-based monomers include itaconic anhydride, citraconic anhydride, 5-norbornene-2,3-dicarboxylic anhydride, maleic anhydride, and the like. Anhydride-based monomers may be used alone or in combination of two or more.
[0072] The melt flow rate (MFR) of the above-mentioned PFA is preferably 0.1 g / 10 min to 50 g / 10 min, more preferably 0.5 g / 10 min to 40 g / 10 min, and further preferably 1.0 g / 10 min to 30 g / 10 min. It should be noted that in this specification, MFR is a value measured under the conditions of a temperature of 372° C. and a load of 5.0 kg according to ASTM D3307.
[0073] As the above-mentioned FEP, there is no particular limitation, but a copolymer in which the molar ratio of TFE units to HFP units (TFE units / HFP units) is 70 / 30 or more and less than 99 / 1 is preferred. A more preferred molar ratio is 70 / 30 or more and 98.9 / 1.1 or less, and a further preferred molar ratio is 80 / 20 or more and 97 / 3 or less. If the TFE unit is too little, the mechanical properties tend to decrease; if it is too much, the melting point is too high and the moldability tends to decrease. FEP is also preferably a copolymer in which the monomer units from monomers copolymerizable with TFE and HFP are 0.1 mol% to 10 mol%, and the total of TFE units and HFP units is 90 mol% to 99.9 mol%. As monomers copolymerizable with TFE and HFP, alkyl perfluorovinyl ether derivatives can be cited.
[0074] The melting point of the FEP is preferably 150 to 320° C., more preferably 200 to 300° C., and even more preferably 240 to 280° C. The melting point is a temperature corresponding to a maximum value in a heat of fusion curve when the temperature is increased at a rate of 10° C. / min using a differential scanning calorimeter [DSC].
[0075] The MFR of the FEP is preferably 0.01 to 100 g / 10 min, more preferably 0.1 to 50 g / 10 min, further preferably 1 to 40 g / 10 min, particularly preferably 1 to 30 g / 10 min.
[0076] The fluororesin film of the present disclosure may also contain components other than fluororesin. The components that may be contained are not particularly limited, and examples thereof include fillers such as silica particles and glass short fibers, and fluorine-free thermosetting resins / thermoplastic resins. The content of components other than fluororesin is not particularly limited, but is more preferably 80% by mass or less, and further preferably 70% by mass or less.
[0077] The fluororesin-containing composition of the present disclosure may contain spherical silica particles, which improves the fluidity of the resin and facilitates molding even when a large amount of silica is blended.
[0078] The above-mentioned spherical silica particles refer to particles whose shape is close to a true sphere. Specifically, the sphericity is preferably above 0.80, more preferably above 0.85, further preferably above 0.90, and most preferably above 0.95. The sphericity is calculated as follows: a photograph is taken using an SEM, and the area and perimeter of the observed particles are calculated as a value calculated by (sphericity) = {4π×(area) ÷ (perimeter) 2}. The closer to 1, the closer to a true sphere. Specifically, the average value of 100 particles measured using an image processing device (Spectris Co., Ltd.: FPIA-3000) is used.
[0079] For the above-mentioned spherical silica particles, when the volume is integrated from the side with a smaller particle size, preferably D90 / D10 is 2 or more (preferably 2.3 or more, 2.5 or more), and D50 is 10 μm or less. Furthermore, D90 / D50 is preferably 1.5 or more (more preferably 1.6 or more). D50 / D10 is preferably 1.5 or more (more preferably 1.6 or more). Since spherical silica particles with a small particle size may enter the gaps between spherical silica particles with a large particle size, the filling property is excellent and the fluidity can be improved. In particular, as a particle size distribution, it is preferred that the frequency of the side with a smaller particle size is larger than that of a Gaussian curve. The particle size can be measured using a laser diffraction scattering particle size distribution measuring device. In addition, it is preferred to remove coarse particles with a particle size larger than a specified particle size using a filter or the like.
[0080] The water absorption of the spherical silica particles is preferably 1.0% or less, and more preferably 0.5% or less. The water absorption is based on the mass of the silica particles when dried. In the measurement of water absorption, the sample in a dry state is placed at 40°C 80% RH for 1 hour, and the water generated by heating at 200°C is measured using a Karl Fischer moisture meter, and the water absorption is calculated.
[0081] Alternatively, the spherical silica particles may be prepared by heating the fluororesin composition at 600° C. for 30 minutes in an air atmosphere to burn off the fluororesin, taking out the spherical silica particles, and then measuring the above parameters by the above methods.
[0082] The silica powder of the present invention may be surface treated. By previously performing the surface treatment, aggregation of the silica particles can be suppressed, and the silica particles can be well dispersed in the resin composition.
[0083] The surface treatment is not particularly limited, and any known surface treatment can be used. Specifically, for example, treatment with silane coupling agents such as epoxy silane, amino silane, vinyl silane, acrylic silane, hydrophobic alkyl silane, phenyl silane, and fluoroalkyl silane having a reactive functional group, plasma treatment, fluorination treatment, etc. can be cited.
[0084] Examples of the silane coupling agent include epoxysilanes such as γ-glycidoxypropyltriethoxysilane and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, aminosilanes such as aminopropyltriethoxysilane and N-phenylaminopropyltrimethoxysilane, vinylsilanes such as vinyltrimethoxysilane, and acrylsilanes such as acryloxytrimethoxysilane.
[0085] The spherical silica can use commercially available silica particles that satisfy the above properties. As commercially available silica particles, for example, Denka fused silica FB grade (manufactured by Denka Co., Ltd.), Denka fused silica SFP grade (manufactured by Denka Co., Ltd.), EXCELICA (manufactured by Tokuyama Co., Ltd.), high-purity synthetic spherical silica ADMAFINE (manufactured by Admatechs Co., Ltd.), ADMANANO (manufactured by Admatechs Co., Ltd.), ADMAFUSE (manufactured by Admatechs Co., Ltd.), etc. can be cited.
[0086] In the case of mixing the above-mentioned spherical silica, about its mixing amount, relative to the mass of the fluororesin strip film, the mixing ratio of silica is preferably greater than 40% by mass. By setting the mixing ratio to the above range, it is possible to achieve a balance between the linear expansion coefficient and the moldability, which is preferred from the perspective of being easy to make a fluororesin composition having both properties. The above ratio is more preferably 50% by mass or more, and more preferably 60% by mass or more. The upper limit of the above ratio is not particularly limited, and is more preferably 80% by mass or less, and more preferably 70% by mass or less.
[0087] (Method for producing long fluororesin film of the present disclosure)
[0088] In addition to using a fluororesin with a small number of unstable functional groups as described above, the fluororesin long strip film disclosed herein also needs to improve uniformity in its manufacturing method. The fluororesin long strip film disclosed herein is generally manufactured by extrusion melt molding as follows: the molten resin is extruded from a T-die to be molded into a film shape, and after cooling, the film is rolled up to manufacture.
[0089] In such extrusion melt molding, the thickness of the resin film is particularly affected by the air gap distance from the end of the T-die where the resin flows out to the initial contact with the roller, the MFR of the resin used, the melting temperature and pressure during film production, the slit width of the T-die, the gap width, etc. Therefore, by appropriately adjusting these, a smooth resin film that satisfies the above parameters can be obtained.
[0090] The air gap distance from the end of the T-die where the resin flows out to the contact with the first roll is preferably 65 mm or less. That is, by shortening the air gap, the presence of the air layer between the melt and the first roll is reduced, thereby reducing the unevenness of the film thickness.
[0091] Furthermore, it is also preferred to adjust the MFR. The lower the viscosity of the molten resin, the more the inclusion of the air layer increases, so the melt flow rate (MFR) is preferably 0.1 g / 10 min to 50 g / 10 min, more preferably 0.5 g / 10 min to 40 g / 10 min, and further preferably 1.0 g / 10 min to 30 g / 10 min. The above MFR is a value measured under the measurement conditions described in the examples.
[0092] In addition, the melting temperature is preferably adjusted, and it is preferred to select a temperature range that can obtain the above-mentioned MFR value. Specifically, the appropriate melting temperature varies depending on the type of resin, the molecular weight of the resin, etc., but it is preferably adjusted to set the temperature in the range of 340°C to 370°C so that the MFR of the resin is within the specified range.
[0093] (Surface oxygen ratio)
[0094] The oxygen element ratio of the film disclosed herein when measured by ESCA on one or both surfaces after heat treatment at 180° C. for 3 minutes may be 1.5 atomic % or more, more preferably 1.8 atomic % or more, and even more preferably 2.0 atomic % or more.
[0095] Fluororesin films generally have low adhesion to other raw materials. Therefore, in order to improve adhesion when bonding to other raw materials, the film obtained by extrusion molding can be surface treated to increase the oxygen element ratio to improve adhesion, so that the oxygen element ratio on the surface is within the above range.
[0096] The film disclosed herein may be a fluorine film having a difference of 1.0 atomic % or more between the oxygen element ratio when the surface state is measured by a scanning X-ray photoelectron spectroscopy analyzer (XPS / ESCA) and the oxygen element ratio when the film is etched in the depth direction by an argon cluster ion beam at an incident angle of 45° for 15 minutes and measured by a scanning X-ray photoelectron spectroscopy analyzer (XPS / ESCA). By increasing only the oxygen element ratio on the surface that contributes to bonding, sufficient bonding strength can be obtained without impairing dielectric properties.
[0097] The heat treatment at 180° C. for 3 minutes is performed by placing the film on a metal tray and performing the treatment in an electric furnace under an air atmosphere.
[0098] When the fluororesin film of the present disclosure is laminated with a different material, it is preferred to use a film in which the absolute values of the dimensional change rates in MD and TD before and after the heat treatment are 1.0% or less when measured after cooling to 25°C after heat treatment at 180°C for 10 minutes. In the present disclosure, regarding the dimensional change rate, a film sample cut into 300 mm squares is provided with points at intervals of 180 mm, and heat treated for 10 minutes in an electric furnace set at 180°C in an air atmosphere without applying a load, and then cooled to 25°C. The intervals between the points in the MD direction and the TD direction of the cooled film are measured, and the dimensional change rate is calculated from the amount of change in the intervals between the points before and after the heat treatment.
[0099] In order to obtain a fluororesin film having such a dimensional change rate, it is preferable to perform an annealing treatment as described in detail below.
[0100] The resin film disclosed herein preferably has a dielectric loss tangent of less than 0.0015 at 10 GHz. This range is preferred because the loss of electrical signals in the circuit can be suppressed to a low level. The dielectric loss tangent is more preferably less than 0.0013, and further preferably less than 0.0010.
[0101] In order to make the dielectric loss tangent within the above range, it is preferable to use a resin having a small number of unstable functional groups, and it is more preferable to use a fluorinated fluorine resin.
[0102] The bonding strength of the fluororesin film when bonded to a metal foil having a surface roughness Rz of 1.5 μm or less using a vacuum hot press under the conditions of a temperature of at least the melting point and not more than the melting point + 30°C, a pressure of 1.5 MPa to 3.0 MPa, and a time of 300 seconds to 600 seconds is preferably 0.8 N / mm or more. The bonding strength herein refers to the bonding strength measured under the conditions described in the examples for the laminate bonded under the above conditions.
[0103] The specific method of the surface modification is not particularly limited, and the surface modification can be performed by any known method. It should be noted that such surface modification can be performed on the obtained resin film having excellent thickness uniformity by the method described above.
[0104] The surface modification of the fluororesin film can be carried out by a discharge treatment based on corona discharge treatment, glow discharge treatment, plasma discharge treatment, sputtering treatment, etc., which has been carried out in the past. For example, in addition to controlling the surface free energy by introducing oxygen, nitrogen, hydrogen, etc. into the discharge atmosphere, the surface to be modified is exposed to an atmosphere of an inert gas containing an organic compound as an inert gas containing an organic compound, and a high-frequency voltage is applied between electrodes to generate a discharge, thereby generating active species on the surface, and then introducing functional groups of organic compounds or graft-polymerized organic compounds, thereby surface modification can be carried out. Examples of the above-mentioned inert gas include nitrogen, helium, argon, etc.
[0105] Examples of the organic compound in the above-mentioned inert gas containing organic compounds include polymerizable or non-polymerizable organic compounds containing oxygen atoms, such as vinyl esters such as vinyl acetate and vinyl formate; acrylic esters such as glycidyl methacrylate; ethers such as vinyl ethyl ether, vinyl methyl ether, and glycidyl methyl ether; carboxylic acids such as acetic acid and formic acid; alcohols such as methanol, ethanol, phenol, and ethylene glycol; ketones such as acetone and methyl ethyl ketone; carboxylic acid esters such as ethyl acetate and ethyl formate; acrylic acids such as acrylic acid and methacrylic acid, etc. Among these, vinyl esters, acrylic esters, and ketones are preferred, and vinyl acetate and glycidyl methacrylate are particularly preferred, from the perspective of the surface being less likely to be deactivated after modification, that is, having a long life, and being easy to handle.
[0106] The concentration of the organic compound in the above-mentioned inert gas containing organic compounds varies depending on the type of organic compound, the type of fluororesin to be surface-modified, etc., and is usually 0.1 volume % to 3.0 volume %, preferably 0.1 volume % to 1.0 volume %. The discharge conditions can be appropriately selected according to the degree of surface modification as the target, the type of fluororesin, the type or concentration of the organic compound, etc. Usually, when the discharge amount is 50W·min / m 2 ~1500W·min / m 2 , preferably 70W·min / m 2 Above 1400W·min / m 2The discharge treatment is carried out within the following range. The treatment temperature can be carried out at any temperature in the range of 0°C to 100°C. Due to concerns about elongation and wrinkles of the film, it is preferably below 80°C. Regarding the degree of surface modification, considering that the adhesion of the surface is reduced due to heat during post-processing, the presence ratio of oxygen elements when observed by ESCA is 2.0% or more, preferably 2.5% or more, more preferably 3.0% or more, and further preferably 3.5% or more. There is no particular provision on the upper limit, but in view of the impact on productivity and other physical properties, it is preferably 25.0% or less. There is no particular provision on the presence ratio of nitrogen elements, but it is preferably 0.1% or more. In addition, the thickness of a fluororesin film is preferably 2.5μm to 1000μm, more preferably 5μm to 500μm, and further preferably 12.5μm to 150μm.
[0107] (Annealing treatment)
[0108] The fluororesin film of the present disclosure may be subjected to annealing treatment after the above-mentioned surface treatment. As mentioned above, the fluororesin film of the present disclosure is required to have dimensional stability when bonded to a metal foil. Therefore, it is preferred that the shrinkage rate during heating is low.
[0109] Fluororesin films obtained by extrusion melt molding often experience thermal shrinkage due to residual internal stress, and such thermal shrinkage can adversely affect dimensional stability when laminated with metal foil. Therefore, it is preferred to relax the internal stress by annealing. Annealing can be performed by heat treatment. The heat treatment can be performed, for example, by passing through a heating furnace in a roll-to-roll manner.
[0110] In the manufacture of the fluororesin film disclosed herein, it is preferred to perform annealing after the above-mentioned corona discharge treatment. In addition, sometimes heat treatment is performed in the process of laminating the film with other materials such as metal foil. Therefore, by undergoing these heat treatments, the amount of oxygen on the surface of the fluororesin film is reduced. Thus, it is preferred to perform surface modification under the condition of obtaining sufficient surface oxygen amount when the fluororesin film is actually laminated with other materials such as metal foil.
[0111] The annealing temperature is preferably higher than the glass transition temperature - 20°C and lower than the melting point, more preferably higher than the glass transition temperature and lower than the melting point - 20°C, and further preferably higher than the glass transition temperature and lower than the melting point - 60°C. The annealing time is not particularly limited and may be appropriately adjusted within a range of, for example, 0.5 to 60 minutes.
[0112] When heating in the roll-to-roll manner, the tension can be appropriately adjusted according to the film thickness, set temperature, etc., and is preferably 20 N / m or less. By heating under such conditions, internal stress can be fully relaxed and dimensional changes will not occur, which is preferred.
[0113] The order of the surface treatment and the annealing treatment is not particularly limited, and the number of times each step is performed is not limited to once, but may be performed twice or more.
[0114] The fluororesin film disclosed herein can be used as a sheet for printed wiring board and laminated with other substrates. The thickness of the fluororesin film disclosed herein is preferably 2.5 μm to 1000 μm, more preferably 5 μm to 500 μm, and further preferably 7 μm to 150 μm. The thickness can be selected in consideration of the balance between the electrical properties and the linear expansion coefficient of the laminate.
[0115] The present disclosure also relates to a laminate, characterized in that a metal foil is bonded to one or both sides of the above-mentioned fluororesin film. As described above, the film containing fluororesin of the present disclosure has excellent adhesion and excellent uniformity of thickness. Therefore, in order to eliminate the ribs from the ribs during lamination, lamination can be performed without applying excessive tension to the film, so that lamination can be performed while suppressing the internal stress remaining in the laminated film, which is also preferred in terms of not causing curling as a laminate.
[0116] The Rz of the metal foil is preferably 1.5 μm or less. That is, the fluororesin composition of the present disclosure also has excellent adhesion to a metal foil with a high smoothness and an Rz of 1.5 μm or less. Furthermore, the metal foil only needs to have a surface with a thickness of 1.5 μm or less on which at least the surface of the metal foil is bonded to the fluororesin film, and the Rz value of the other surface is not particularly limited.
[0117] The thickness of the metal foil is not particularly limited, but is preferably in the range of 1 μm to 100 μm, more preferably in the range of 5 μm to 50 μm, and even more preferably in the range of 9 μm to 35 μm.
[0118] The metal foil is not particularly limited, but is preferably a copper foil. The copper foil is not particularly limited, and specific examples thereof include a rolled copper foil and an electrolytic copper foil.
[0119] The copper foil having an Rz of 1.5 μm or less is not particularly limited, and commercially available copper foil can be used. Examples of commercially available copper foil having an Rz of 1.5 μm or less include electrolytic copper foil CF-T9DA-SV-18 (thickness 18 μm / Rz 0.85 μm) (manufactured by Fukuda Metal Foil Co., Ltd.).
[0120] The metal foil may be subjected to a surface treatment in order to improve the bonding strength with the fluororesin film of the present disclosure.
[0121] The surface treatment is not particularly limited, and is silane coupling treatment, plasma treatment, corona treatment, UV treatment, electron beam treatment, etc. The reactive functional group of the silane coupling agent is not particularly limited. From the aspect of adhesion to the resin substrate, it is preferred to have at least one selected from amino, (meth) acryloyl, mercapto and epoxy groups at the terminal. In addition, the hydrolyzable group is not particularly limited, and alkoxy groups such as methoxy and ethoxy can be cited. The metal foil used in the present disclosure can be formed with a rust-proof layer (oxide film such as chromate, etc.), a heat-resistant layer, etc.
[0122] The surface-treated metal foil having the surface-treated layer formed of the above-mentioned silane compound on the surface of the metal foil can be produced by preparing a solution containing the silane compound and then surface-treating the metal foil with the solution.
[0123] The metal foil may have a roughening treatment layer on its surface in order to improve adhesion to the resin substrate.
[0124] It should be noted that, if the roughening treatment may reduce the performance required by the present disclosure, the roughening particles electrodeposited on the surface of the metal foil may be reduced as needed, or the roughening treatment may not be performed.
[0125] From the perspective of improving various properties, one or more layers selected from the group consisting of a heat-resistant treatment layer, a rust-proof treatment layer, and a chromate treatment layer may be provided between the metal foil and the surface treatment layer. These layers may be a single layer or multiple layers.
[0126] In the above-mentioned laminate, the bonding strength between the metal foil and the fluororesin film is preferably 0.8N / mm or more. By applying the above-mentioned method, such bonding strength can be achieved. By making the bonding strength 0.9N / mm or more, and further 1.0N / mm or more, it can be suitable for use as a metal-coated laminate and a circuit substrate. It should be noted that the bonding strength herein refers to the bonding strength measured under the conditions described in the embodiments. In addition, in the case of a laminate in which the metal foil is bonded to the surface-treated surface of the fluororesin film that has been surface-treated on only one side, in order to improve the adhesion between the laminate and other materials, the surface of the fluororesin film that has not been surface-treated can also be subjected to surface modification.
[0127] The metal-clad laminate of the present disclosure may further include a layer other than the metal foil and the fluororesin film. The layer other than the metal foil and the fluororesin film is preferably at least one selected from the group consisting of polyimide, liquid crystal polymer, polyphenylene sulfide, cycloolefin polymer, polystyrene, epoxy resin, bismaleimide, polyphenylene oxide, polyphenylene ether and polybutadiene.
[0128] The layers other than the metal foil and the fluororesin film are not particularly limited as long as they are composed of the above-mentioned resin. The thickness of the layers other than the metal foil and the fluororesin film is preferably within a range of 12.5 μm to 260 μm.
[0129] The laminate structure of the metal-clad laminate disclosed in the present invention can be suitably used not only for long strips of metal-clad laminates having metal foil laminated on one or both sides of a roll film, but also for metal-clad laminates having metal foil laminated on a cut roll film.
[0130] The metal-coated laminate disclosed in the present invention unwinds the roll film of the present invention and forms a metal layer on its surface. The metal layer may be formed on one side or both sides of the roll film. As a method for forming a metal layer, there may be cited a method of laminating (bonding) a metal foil on the surface of the roll film, a vapor deposition method, a plating method, and the like. As a method of laminating a metal foil, there may be cited a method of utilizing hot pressing. The hot pressing temperature may be cited as the melting point of the dielectric film -150°C to the melting point of the dielectric film +40°C. The hot pressing time is, for example, 1 minute to 30 minutes. It can be manufactured by a method in which the hot pressing pressure is 0.1MPa to 10MPa.
[0131] The use of the metal-coated laminate disclosed in the present invention is not particularly limited, and it is used as a circuit substrate. A printed substrate refers to a plate-like component that is configured and fixed in a limited space while electrically connecting electronic components such as semiconductors and capacitor chips. There are no particular restrictions on the composition of the printed substrate formed by the present metal-coated laminate. The printed substrate can be any of a rigid substrate, a flexible substrate, and a rigid-flexible substrate. The printed substrate can be any of a single-sided substrate, a double-sided substrate, and a multi-layer substrate (build-up substrate, etc.). It is particularly suitable for use in flexible substrates and rigid substrates.
[0132] The circuit board is not particularly limited, and can be produced by a general method using the above-mentioned metal-clad laminate.
[0133] The laminate for the circuit board may also be a laminate having a metal foil layer, the above-mentioned fluororesin film and a substrate layer. The substrate layer is not particularly limited, but preferably has a cloth layer made of glass fiber and a resin film layer.
[0134] The above-mentioned cloth layer composed of glass fibers is a layer composed of glass cloth, glass nonwoven fabric, etc. As the glass cloth, commercially available glass cloth can be used. In order to improve the affinity with the fluororesin, it is preferably treated with a silane coupling agent. As the material of the glass cloth, E glass, C glass, A glass, S glass, D glass, NE glass, low dielectric constant glass, etc. can be cited. From the perspective of easy availability, E glass, S glass, and NE glass are preferred. As for the weaving method of the fiber, it can be plain or twill. The thickness of the glass cloth is usually 5μm to 90μm, preferably 10μm to 75μm, and it is preferred to use a glass cloth thinner than the fluororesin film used.
[0135] The laminate can use glass nonwoven fabric as the cloth layer composed of glass fiber. Glass nonwoven fabric is a material formed by bonding short glass fibers with a small amount of binder compound (resin or inorganic substance), or a material that maintains its shape by winding glass short fibers without using a binder compound, and commercial products can be used. The diameter of the glass short fibers is preferably 0.5 μm to 30 μm, and the fiber length is preferably 5 mm to 30 mm. As specific examples of binder compounds, resins such as epoxy resins, acrylic resins, cellulose, polyvinyl alcohol, and fluororesins, or inorganic substances such as silica compounds can be cited. The amount of binder compound used is usually 3% to 15% by mass relative to the glass short fibers. As the material of the glass short fibers, E glass, C glass, A glass, S glass, D glass, NE glass, low dielectric constant glass, etc. can be cited. The thickness of the glass nonwoven fabric is usually 50 μm to 1000 μm, preferably 100 μm to 900 μm. It should be noted that the thickness of the glass nonwoven fabric in the present application refers to the value measured using a digital gauge DG-925 (load 110 g, surface diameter 10 mm) manufactured by Ono Sakuki Co., Ltd. in accordance with JIS P8118: 1998. The glass nonwoven fabric may be treated with a silane coupling agent to improve affinity with fluororesin.
[0136] Since the porosity of most glass nonwoven fabrics is 80% or more, which is very high, it is preferable to use a glass nonwoven fabric thicker than the sheet made of fluororesin and compress it by pressure.
[0137] The cloth layer composed of the glass fiber may be a layer formed by laminating glass cloth and glass nonwoven fabric. In this way, the properties of each other are combined to obtain appropriate properties.
[0138] The cloth layer composed of the glass fiber may be in the state of a prepreg impregnated with a resin.
[0139] In the above-mentioned laminate, the cloth layer composed of glass fibers and the fluororesin film may be bonded at the interface, or the fluororesin film may be partially or entirely impregnated into the cloth layer composed of glass fibers.
[0140] In addition, a fluororesin composition may be impregnated into a cloth made of glass fiber to prepare a prepreg. The prepreg thus obtained may be further laminated with the fluororesin film disclosed herein. In this case, the fluororesin composition used in preparing the prepreg is not particularly limited, and the fluororesin film disclosed herein may also be used.
[0141] As the resin film used as the substrate layer, a heat-resistant resin film and a thermosetting resin film are preferred. Examples of the heat-resistant resin film include polyimide, liquid crystal polymer, polyphenylene sulfide, etc. Examples of the thermosetting resin include thermosetting resins including epoxy resins, bismaleimide, polyphenylene oxide, polyphenylene ether, polybutadiene, etc.
[0142] The heat-resistant resin film and the thermosetting resin film may contain reinforcing fibers. The reinforcing fibers are not particularly limited, but are preferably glass cloth, and particularly low dielectric constant reinforcing fibers.
[0143] The dielectric properties, linear expansion coefficient, water absorption rate and other properties of the heat-resistant resin film and the thermosetting resin film are not particularly limited. For example, the dielectric constant at 20 GHz is preferably 3.8 or less, more preferably 3.4 or less, and further preferably 3.0 or less. The dielectric loss tangent at 20 GHz is preferably 0.0030 or less, more preferably 0.0025 or less, and further preferably 0.0020 or less. The linear expansion coefficient is preferably 100 ppm / °C or less, more preferably 70 ppm / °C or less, and further preferably 40 ppm / °C or less. The water absorption rate is preferably 1.0% or less, more preferably 0.5% or less, and further preferably 0.1% or less.
[0144] Example
[0145] The present disclosure is specifically described below based on examples. In the following examples, the ratio is expressed as a molar ratio.
[0146] Example 1
[0147] The pellets with copolymer composition TFE / PPVE=98.6 / 1.4, MFR15.2g / 10min, and melting point of 309.5℃ were put into an extruder at 360℃, extruded from a 1700mm wide T-die and pulled to a metal cooling roller, and then wound on a winding core to make a 1300mm wide, 50μm thick roll film. The air gap at this time was set to 60mm. The film was further corona treated on both sides to obtain an unstable functional group number of 324 (10 carbon atoms / 10 6It should be noted that the corona treatment is a surface treatment of both sides of the roll film obtained by extrusion (nitrogen containing 0.50 volume % vinyl acetate is circulated near the discharge electrode and the roll ground electrode of the corona discharge device, and the film is continuously passed along the roll ground electrode at a discharge rate of 1324 W·min / m 2 Both sides of the film were treated with corona discharge).
[0148] Example 2
[0149] The same as Example 1 except that the pellets with copolymer composition TFE / PPVE=98.2 / 1.8, MFR 15.8 g / 10 min, and melting point 305.3°C were used. In addition, both sides of the film were corona treated to obtain a film with 307 unstable functional groups (each with 10 carbon atoms). 6 ) roll film.
[0150] Furthermore, an annealing treatment was performed at 180° C. for 2 minutes while applying a conveying tension of 0.5 N.
[0151] The roll film was unwound and cut into 15 cm in length×15 cm in width, and an electrolytic copper foil CF-T9DA-SV18 (thickness 18 μm / Rz 0.85 μm) (Fukuda Metal Foil & Powder Industry Co., Ltd.) of the same size was bonded to one surface, and then a copper-clad laminate was obtained using a vacuum press.
[0152] Example 3
[0153] The procedures were the same as those in Example 2 except that a roll film having a thickness of 25 μm was prepared.
[0154] Example 4
[0155] The procedures were the same as those in Example 3 except that a roll film having a thickness of 12.5 μm was prepared.
[0156] Example 5
[0157] The copolymer composition of Example 1 was TFE / PPVE=97.5 / 2.5, MFR 21.0 g / 10 min, melting point 303°C, glass transition temperature 93°C, and the other aspects were the same. In addition, both sides of the film were corona treated to obtain an unstable functional group number of 201 (number / carbon number 10 6 ) roll film.
[0158] Example 6
[0159] The same as Example 1 except that the pellets with copolymer composition TFE / PPVE=97.7 / 2.3, MFR14.6g / 10min, and melting point 300.9°C were used. In addition, both sides of the film were corona treated to obtain a film with 192 unstable functional groups (each having 10 carbon atoms). 6 ) roll film.
[0160] Example 7
[0161] The same as in Example 1 except that the pellets with copolymer composition TFE / PPVE / HFP=98.5 / 1.1 / 0.4 and MFR24.0 g / 10 min were used. In addition, both sides of the film were corona treated to obtain a film with 126 unstable functional groups (10 carbon atoms / 10 6 ) roll film.
[0162] Example 8
[0163] The same procedures were followed as in Example 7 except that a roll film having a thickness of 25 μm was produced.
[0164] Example 9
[0165] The same procedures were followed as in Example 7 except that a roll film having a thickness of 12.5 μm was produced.
[0166] Example 10
[0167] The same as Example 1 except that the pellets with copolymer composition TFE / PPVE=97.7 / 2.3, MFR14.8g / 10min, and melting point 300.9°C were used. In addition, both sides of the film were corona treated to obtain a film with 38 unstable functional groups (each with 10 carbon atoms). 6 ) roll film.
[0168] Embodiment 11
[0169] The copolymer composition of Example 1 was TFE / PPVE=97.4 / 2.6, MFR 25.0 g / 10 min, melting point 304°C, glass transition temperature 93°C, and the other aspects were the same. In addition, both sides of the film were corona treated to obtain an unstable functional group number of 15 (units / carbon number 10 6 ) roll film.
[0170] Example 12
[0171] The same as Example 1 except that a pellet having a copolymer composition of TFE / PPVE = 97.7 / 2.3, an MFR of 15.0 g / 10 min, and a melting point of 300.9°C was used. In addition, both sides of the film were corona treated to obtain a film having 8 unstable functional groups (each having 10 carbon atoms). 6) roll film.
[0172] Embodiment 13
[0173] The procedures were the same as those of Example 12 except that a roll film having a thickness of 25 μm was prepared.
[0174] Embodiment 14
[0175] The procedures were the same as those of Example 12 except that a roll film having a thickness of 12.5 μm was prepared.
[0176] Embodiment 15
[0177] The same procedures were followed as in Example 12, except that the film was extruded from a 1000 mm wide T-die, drawn onto a metal cooling roll, and further wound up on a winding core to produce a 500 mm wide roll film.
[0178] Example 16
[0179] The same procedures were followed as in Example 15 except that a roll film having a thickness of 25 μm was produced.
[0180] Embodiment 17
[0181] The procedures were the same as those of Example 15 except that a roll film having a thickness of 12.5 μm was prepared.
[0182] Embodiment 18
[0183] The same procedures were followed as in Example 15 except that the air gap was set to 50 mm.
[0184] Comparative Example 1
[0185] The same procedures were followed as in Example 15 except that the air gap was set to 70 mm.
[0186] Comparative Example 2
[0187] The same procedures were followed as in Example 15 except that the air gap was set to 80 mm.
[0188] Comparative Example 3
[0189] The air gap was 70 mm, which was the same as in Example 2. In addition, both sides of the film were corona treated to obtain an unstable functional group number of 307 (number / carbon number 10 6 ) roll film.
[0190] Comparative Example 4
[0191] The same as in Example 1 except that the pellets with copolymer composition TFE / PPVE=98.2 / 1.8 and MFR14.0 g / 10 min were used. In addition, both sides of the film were corona treated to obtain a film with 390 unstable functional groups (each having 10 carbon atoms).6 ) roll film.
[0192] Comparative Example 5
[0193] The procedures were the same as those of Comparative Example 4 except that a roll film having a thickness of 25 μm was prepared.
[0194] Comparative Example 6
[0195] The procedures were the same as those of Comparative Example 4 except that a roll film having a thickness of 12.5 μm was prepared.
[0196] Comparative Example 7
[0197] The same as Example 1 except that the pellets with copolymer composition TFE / PPVE=97.2 / 2.8, MFR 64.0 g / 10 min, melting point 284°C, and glass transition temperature 90°C were used. In addition, both sides of the film were corona treated to obtain a film with 507 unstable functional groups (each carbon atom 10 6 ) roll film.
[0198] (Evaluation method)
[0199] (per 1×10 6 The number of unstable functional groups in the main chain carbon atoms)
[0200] The analysis was performed using FT-IR Spectrometer 1760X (manufactured by Perkin-Elmer).
[0201] (Glass transition temperature)
[0202] The dynamic viscoelasticity was determined using DVA-220 (manufactured by IT Instruments & Control Co., Ltd.) A compression-molded piece with a length of 25 mm, a width of 5 mm, and a thickness of 0.2 mm was used as a sample test piece, and the temperature at the peak of the tan δ value was taken as the glass transition temperature at a heating rate of 5°C / min and a frequency of 10 Hz.
[0203] (Film width)
[0204] The measurement was carried out using a curved iron ruler.
[0205] (Film thickness)
[0206] Regarding thickness, Figure 1As shown, the film thickness is measured every 5 mm relative to the same width direction. The measurement uses a table-top offline contact thickness measuring device manufactured by Sanwen Electric. Furthermore, in the direction of travel, the thickness is measured at 12 locations every 20 cm, and the film thickness is measured every 5 mm. The average of all the film thicknesses measured in this way is shown in the table as the "average film thickness of the surface" (a). Furthermore, when the values are the same relative to the width direction, the average values of the 12 thicknesses measured in the direction of travel are calculated, and the difference between the maximum value (b) and the average film thickness (a) of the surface is calculated.
[0207] (Air Gap)
[0208] The distance from the tip of the die lip where the molten resin exits the T-die to the point where the molten resin first comes into contact with the roller was measured using a bent iron ruler.
[0209] (Strong muscles)
[0210] The formed roll film was stored in a warehouse where the temperature and humidity were not controlled, and the film was evaluated for cracking after being placed for 1 month. The film cracking evaluation method was that if cracking was observed with the naked eye, it was considered to be present; if cracking was not observed, it was considered to be absent.
[0211] (Shape: Curl or not)
[0212] A fluororesin film that was not preheated or preheated at a temperature above the glass transition temperature and below the melting point was used, and the copper foil / fluororesin film was stacked in this order to form a 100 mm square laminate produced by vacuum hot pressing, and the presence or absence of curling was visually confirmed. The copper foil used was electrolytic copper foil CF-T9DA-SV-18 (thickness 18 μm / Rz 0.85 μm) (manufactured by Fukuda Metal Foil Powder Industry Co., Ltd.).
[0213] (Shrinkage rate after copper foil etching)
[0214] The annealed film and electrolytic copper foil CF-T9DA-SV-18 (thickness 18 μm / Rz 0.85 μm) (manufactured by Fukuda Metal Foil Powder Industry Co., Ltd.) were hot pressed using a vacuum hot press (model: MKP-1000HVWH-S7 / manufactured by MIKADO TECHNOS Co., Ltd.) at a pressing temperature of 320°C, a preheating time of 60 seconds, a pressure of 1.5 MPa, and a pressing time of 300 seconds, thereby bonding the surface treated surface of the fluororesin film to the copper foil. The fluorine film surfaces of the two obtained single-sided copper clad laminates were surface treated respectively, and they were layered in the order of 1 single-sided copper clad laminate / 1 prepreg R-5680 (N) (thickness 80 μm) (manufactured by Panasonic Corporation) / 1 single-sided copper clad laminate in a manner that the surface treated surface was consistent with the prepreg, and they were bonded using a vacuum hot press at a pressing temperature of 200°C to obtain a double-sided copper clad laminate.
[0215] After measuring the dimensions of the produced double-sided copper-clad laminate, the copper foils on both sides were removed, and the dimensions were further measured after heating at 150° C. for 30 minutes, and then the change rate was calculated.
[0216] (Characteristic impedance)
[0217] The annealed film and electrolytic copper foil CF-T9DA-SV-18 (thickness 18 μm / Rz 0.85 μm) (manufactured by Fukuda Metal Foil Powder Industry Co., Ltd.) were hot pressed using a vacuum hot press (model: MKP-1000HVWH-S7 / manufactured by MIKADO TECHNOS Co., Ltd.) at a pressing temperature of 320°C, a preheating time of 60 seconds, a pressure of 1.5 MPa, and a pressing time of 300 seconds, thereby bonding the surface treated surface of the fluororesin film to the copper foil. The fluorine film surfaces of the two obtained single-sided copper clad laminates were surface treated respectively, and the surface treated surfaces were matched with the prepreg, and they were layered in the order of 1 single-sided copper clad laminate / 1 prepreg R-5680 (N) (thickness 80 μm) (polyphenylene ether (PPE) resin cured product, manufactured by Panasonic Corporation) / 1 single-sided copper clad laminate. The laminates were bonded using a vacuum hot press at a pressing temperature of 200°C to obtain double-sided copper clad laminates, which were made into substrates, and the characteristic impedance was measured based on the TDR method.
[0218] (MFR)
[0219] The measurement was performed in accordance with ASTM D3307 at a temperature of 372° C. and a load of 5.0 kg.
[0220] (Rz)
[0221] The 200 μm diameter was measured using a color 3D laser microscope VK-9700 manufactured by KEYENCE. 2 Range of Rz.
[0222] (Adhesion Strength)
[0223] The film prepared in Example 2 and electrolytic copper foil CF-T9DA-SV-18 (thickness 18μm / Rz 0.85μm) (manufactured by Fukuda Metal Foil Powder Industry Co., Ltd.) were used, and the copper foil, fluororesin film and copper foil were stacked in this order, and hot pressed using a vacuum hot press (model: MKP-1000HVWH-S7 / manufactured by MIKADO TECHNOS Co., Ltd.) at a pressing temperature of 320°C, a preheating time of 60 seconds, a pressure of 1.5MPa, and a pressing time of 300 seconds. An aluminum plate was attached to one side of the laminate with an adhesive tape, and a Tensilon universal testing machine (manufactured by Shimadzu Corporation) was used to grasp and stretch a 10mm wide copper foil in a direction of 90° relative to the plane of the laminate at a speed of 50mm per minute, thereby measuring the peel strength of the copper foil, and the obtained value was used as the bonding strength. The result was 1.3N / mm.
[0224] (Method for measuring characteristic impedance)
[0225] The annealed film and electrolytic copper foil CF-T9DA-SV-18 (thickness 18 μm / Rz 0.85 μm) (manufactured by Fukuda Metal Foil Powder Industry Co., Ltd.) were hot pressed using a vacuum hot press (model: MKP-1000HVWH-S7 / manufactured by MIKADO TECHNOS Co., Ltd.) at a pressing temperature of 320°C, a preheating time of 60 seconds, a pressure of 1.5 MPa, and a pressing time of 300 seconds, thereby bonding the surface treated surface of the fluororesin film to the copper foil. The fluorine film surfaces of the two obtained single-sided copper-clad laminates were surface treated respectively, and the surface-treated surfaces were matched with the prepreg in the order of 1 single-sided copper-clad laminate / 1 prepreg R-5680 (N) (thickness 80 μm) (polyphenylene ether (PPE) resin cured product, manufactured by Panasonic Corporation) / 1 single-sided copper-clad laminate, and bonded using a vacuum hot press at a pressing temperature of 200°C to obtain a double-sided copper-clad laminate. After that, a substrate with a microstrip line provided on a single side of the copper foil was prepared. The line width of the line was designed so that the characteristic impedance was 50Ω using the thickness of the film, the relative dielectric constant of the material, and the thickness of the copper foil. The probe was brought into contact with both ends of the evaluation substrate, and the characteristic impedance was measured based on the TDR method using a vector network analyzer.
[0226]
[0227]
[0228]
[0229] Industrial Applicability
[0230] The fluororesin long film disclosed in the present invention can be used for a metal-clad laminate for a circuit board, and the like.
Claims
1. A fluororesin long film, characterized in that: It consists of 1×10 6 The invention is composed of a fluororesin having less than 350 unstable functional groups per carbon atom, and the difference between the maximum value of the average film thickness in the traveling direction measured every 5 mm in the width direction and the average film thickness of the entire surface is within 2 μm. 2 . The fluororesin long film according to claim 1 , comprising a tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA) or a tetrafluoroethylene-hexafluoropropylene copolymer (FEP).
3. The fluororesin long film according to claim 1 or 2, wherein For the fluororesin, 6 The number of unstable functional groups per carbon atom is less than 20.
4. The fluororesin long film according to any one of claims 1 to 3, wherein The bonding strength when bonding to a metal foil having a surface roughness Rz of 1.5 μm or less is 0.8 N / mm or more. 5 . The long fluororesin film according to claim 1 , which is used for a metal-clad laminate.
6. A metal-clad laminate, characterized in that: This is obtained by using a metal foil and the fluororesin film according to any one of claims 1 to 5.
7. The metal-clad laminate according to claim 6, further comprising a layer other than the metal foil and the fluororesin film, The layer other than the metal foil and the fluororesin film is at least one selected from the group consisting of polyimide, liquid crystal polymer, polyphenylene sulfide, cycloolefin polymer, polystyrene, epoxy resin, bismaleimide, polyphenylene oxide, polyphenylene ether and polybutadiene.
8. The metal-clad laminate according to claim 6 or 7, wherein: The surface roughness Rz of the metal foil is 1.5 μm or less.
9. The metal-clad laminate according to any one of claims 6 to 8, wherein The bonding strength between the metal foil and the fluororesin film is 0.8 N / mm or more.
10. A circuit substrate, characterized in that: This is obtained by using the metal-clad laminate according to any one of claims 6 to 9.
Citation Information
Patent Citations
Covered electric wire, and coaxial cable
JP2009059690A
Method of manufacturing thermoplastic film
JP2012187874A
Fluorine resin film and method for producing the same
JP2021160856A